2018
DOI: 10.3758/s13428-018-1071-2
|View full text |Cite
|
Sign up to set email alerts
|

Historical evolution of concrete and abstract language revisited

Abstract: This paper investigates the historical (1850s-2000s) evolution of semantics in the English language using contemporaneous, decade-specific computational estimates of word concreteness. Study 1 describes the computational method of generating time-locked estimates of concreteness based on the Corpus of Historic American English, and makes available the computed scores for 25,000 English words over 15 decades. We also report several tests of reliability and validity, demonstrating that our historical concretenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 24 publications
0
61
1
1
Order By: Relevance
“…The present study proposes a new semantic similarity algorithm based on that of Snefjella et al (2019) for estimating the degree of different LPP dimensions in L2 production and uses the algorithm to address the following three research questions:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study proposes a new semantic similarity algorithm based on that of Snefjella et al (2019) for estimating the degree of different LPP dimensions in L2 production and uses the algorithm to address the following three research questions:…”
Section: Methodsmentioning
confidence: 99%
“…The current study adapted and extended the algorithm and procedure proposed by Snefjella et al (2019) for measuring diachronic change in word concreteness to compute LPP dimension scores for the five EFCAMDAT2 sub-corpora representing L2 learners of different proficiency levels. This section describes how our algorithm was implemented.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Hills and Adelman (2015) used the psycholinguistic property of concreteness (i.e., how easy is it for a given word to refer to a specific object or entity) as an indicator of language learnability on the basis of prior findings that concrete words tend to be acquired earlier in life as compared to abstract words (De Groot & Keijzer, 2000). Hills and Adelman analyzed historical corpora of American English and found that the use of concrete language has become more prevalent over the past two centuries (see also Snefjella et al, 2019). Monaghan (2014) investigated the relation between self-report age of acquisition ratings and the rate of lexical evolution for 200 English words that are fundamental in most language vocabularies.…”
Section: Introductionmentioning
confidence: 99%